Understanding your bowels - Heaton, Ken.; British Medical Association (Poole : Family Doctor Publications in association with the British Medical Assciation, 2006)
What we eat and how we live can have enormous effects on the working of our bowels. This book offers practical advice on how many problems can be prevented by a sensible diet and lifestyle
Includes index.
Keywords: Intestine, Large -- Popular works; Intestines -- Diseases -- Popular works